Structural similarities and features of verbal phraseological units and derived verbs in Turkic languages - Рысбaев, A.; Теменовa, Г. (Journal of Oriental Studies, 2017)
The article considers the general structural similarities and features of verbal phraseological units and derived verbs from nominal stems in Kazakh and Turkish languages. The analysis of the structure and verbal part of phraseology in two languages, at first will help to determine the difference of verbal phraseological units from other units of the language, learn and reveal their own features, and on the other hand, in accordance with their external forms it has complicated informative meaning and methods of ways in the formation of this concept.